FLEXURAL AND TENSILE STRENGTH OF RUBBERIZED CONCRETE WITH STEEL TYRE WIRE - Vincent, Sharvin (Universiti Teknologi PETRONAS, 2020)
The concernsiconfronting mankind in the twenty- century include climate change, population rise, resource overconsumption, waste overproduction and growing demands for energy. This also includes the production of scrapirubber tires which is burgeoning at an alarming rate. Compared to hazardousidisposal methods that leaveia trace of environmental problems, using them as a partial aggregateisubstitute of products such as bitumeniand concrete, the increased environmental risk of rubber tire scrap can beitackled. Even now, amid much analysis and experimental research, the use of crumb rubber as a partial fine aggregate replacement in conventionaliconcrete is a flourishing new project. Previous research on the use of Crumb Rubber as a partialifine aggregate substitute in concreteiindicate a substantial improvement in strengthiand durability accompanied byia major decrease in compressive strength, flexural strength and tensile strength.